Previously unknown evolutionary groups dominate the ssDNA gokushoviruses in oxic and anoxic waters of a coastal marine environment - Labonté, Jessica M.; Hallam, Steven J.; Suttle, Curtis A. (Frontiers in Microbiology, 2015)
Metagenomic studies have revealed that ssDNA phages from the family Microviridae subfamily Gokushovirinae are widespread in aquatic ecosystems. It is hypothesized that gokushoviruses occupy specialized niches, resulting in differences among genotypes traversing water column gradients. Here, we use degenerate primers that amplify a fragment of the gene encoding the major capsid protein to examine the diversity of gokushoviruses in Saanich Inlet (SI), a seasonally anoxic fjord on the coast of Vancouver Island, BC, Canada. Amplicon sequencing of samples from the mixed oxic surface (10 m) and deeper anoxic (200 m) layers indicated a diverse assemblage of gokushoviruses, with greater richness at 10 m than 200 m. A comparison of amplicon sequences with sequences selected on the basis of RFLP patterns from eight surface samples collected over a 1-year period revealed that gokushovirus diversity was higher in spring and summer during stratification and lower in fall and winter after deep-water renewal, consistent with seasonal variability within gokushovirus populations. Our results provide persuasive evidence that, while specific gokushovirus genotypes may have a narrow host range, hosts for gokushoviruses in SI consist of a wide range of bacterial taxa. Indeed, phylogenetic analysis of clustered amplicons revealed at least five new phylogenetic groups of previously unknown sequences, with the most abundant group associated with viruses infecting SUP05, a ubiquitous and abundant member of marine oxygen minimum zones. Relatives of SUP05 dominate the anoxic SI waters where they drive coupled carbon, nitrogen, and sulfur transformations along the redoxline; thus, gokushoviruses are likely important mortality agents of these bacteria with concomittant influences on biogeochemical cycling in marine oxygen minimum zones.